Inhibitory Effect of Cinobufagin on L-Type Ca2+ Currents, Contractility, and Ca2+ Homeostasis of Isolated Adult Rat Ventricular Myocytes - Pinya Li; Qiongtao Song; Tao Liu; Zhonglin Wu; Xi Chu; Xuan Zhang; Ying Zhang; Yonggang Gao; Jianping Zhang; Li Chu (The Scientific World Journal)
Cinobufagin (CBG), a major bioactive ingredient of the bufanolide steroid compounds of Chan Su, has been widely used to treat coronary heart disease. At present, the effect of CBG on the L-type Ca2+ current (ICa-L) of ventricular myocytes remains undefined. The aim of the present study was to characterize the effect of CBG on intracellular Ca2+ ([Ca2+]i) handling and cell contractility in rat ventricular myocytes. CBG was investigated by determining its influence on ICa-L, Ca2+ transient, and contractility in rat ventricular myocytes using the whole-cell patch-clamp technique and video-based edge-detection and dual-excitation fluorescence photomultiplier systems. The dose of CBG (10−8 M) decreased the maximal inhibition of CBG by 47.93%. CBG reduced ICa-L in a concentration-dependent manner with an IC50 of 4 × 10−10 M, upshifted the current-voltage curve of ICa-L, and shifted the activation and inactivation curves of ICa-L leftward. Moreover, CBG diminished the amplitude of the cell shortening and Ca2+ transients with a decrease in the time to peak (Tp) and the time to 50% of the baseline (Tr). CBG inhibited L-type Ca2+ channels, and reduced [Ca2+]i and contractility in adult rat ventricular myocytes. These findings contribute to the understanding of the cardioprotective efficacy of CBG.